Ownership of mother and children's health book and complete basic immunization status in slums and poor population - Hargono, Arief (J Public Health Res, 2020)
Background: The percentage of complete immunization in urban areas is higher than rural areas. The purpose of the study was to analyze the relationship between ownership of Maternal and Child Health (MCH) books with Complete Basic Immunization (CBI) coverage in slums and poor areas. Design and Methods: A rapid survey was conducted in selected slums and poor groups based on medical records from Public Health Center. Informants were mothers with a sample of 325 infants aged 12 to 23 months. Results: The lowest coverage of CBI for slum and poor residents is Pasuruan, which is 55.4%. The results of statistical analysis showed that there was a significant relationship between ownership of MCH books and the complete coverage of basic immunization in Malang (P = 0.000; PR = 3.682); Pasuruan (P = 0.002; PR = 1.854); Sidoarjo (P = 0.000; PR = 4.042); Surabaya (P = 0.000; PR = 2.425). Conclusions: It is recommended that the government should improve access to complete immunization programs in slums and poor population.